D.V.I.G.N.V. or a few words about a curiosity found in German books of friendship from the 16th and 17th centuries - Kucharska-Dreiss, Elżbieta (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
Kucharska-Dreiss starts her paper with a brief discussion of the origin, the role and the form of books of friendship (known also as “alba amicorum”). She also presents a general image of the owners of books of friendship, of the authors of inscriptions and of the structure of inscriptions themselves. She closes the introductory part of the paper with the conclusion that a book of friendship is studied by many disciplines. In the next part of her paper Kucharska-Dreiss discusses in more detail the content of Lexikon der Stammbuchsprüche: Stechow’s Stammbuchsprüche-Schlüssel (S.S.S.S.) (Stechow 1996) on which her study is based. The main part of the study (the first of a series of several planned) is devoted to preliminary remarks on the initialisms to be found in books of friendship (i.e. aphorisms, quotations, etc. written down as sequences of initials). The author’s observations concern the length and form of initialisms, multiple solutions of the same initialism (in the same or different sources, in one or several languages, with similar or slightly different content), the cited works (with the Bible as a primary source of quotations) and authors (ancient thinkers, writers and poets were most often cited). Closing her paper, the author informs the reader which (detailed) issues will be explored in further studies belonging to this series of articles.